How did a duplicated gene copy evolve into a restorer-of-fertility gene in a plant? The case of Oma1. Issue 11 (6th November 2019) - Arakawa, Takumi; Sugaya, Hajime; Katsuyama, Takaya; Honma, Yujiro; Matsui, Katsunori; Matsuhira, Hiroaki; Kuroda, Yosuke; Kitazaki, Kazuyoshi; Kubo, Tomohiko
Abstract : Restorer-of-fertility ( Rf ) is a suppressor of cytoplasmic male sterility (CMS), a mitochondrion-encoded trait that has been reported in many plant species. The occurrence of CMS is considered to be independent in each lineage; hence, the question of how Rf evolved was raised. Sugar beet Rf resembles Oma1, a gene for quality control of the mitochondrial inner membrane. Oma1 homologues comprise a small gene family in the sugar beet genome, unlike Arabidopsis and other eukaryotes. The sugar beet sequence that best matched Arabidopsis atOma1 was named bvOma1 ; sugar beet Rf ( RF1-Oma1 ) was another member. During anther development, atOma1 mRNA was detected from the tetrad to the microspore stages, whereas bvOma1 mRNA was detected at the microspore stage and RF1-Oma1 mRNA was detected during the meiosis and tetrad stages. A transgenic study revealed that, whereas RF1-Oma1 can bind to a CMS-specific protein and alter the higher-order structure of the CMS-specific protein complex, neither bvOma1 nor atOma1 show such activity. We favour the hypothesis that an ancestral Oma1 gene duplicated to form a small gene family, and that one of the copies evolved and acquired a novel expression pattern and protein function as an Rf, i.e. RF1-Oma1 evolved via neofunctionalization.